Perbandingan Pekerjaan Kusen dan Pintu Bahan Kayu dengan Bahan Alumunium - Michael Tedja; Irfan Balindo Sidauruk; Ricky Rahmadyansah (Bina Nusantara University, 2015)
Sills, doors and windows is one of the most important parts of the buildings, one type of building that needs them is residences. Nowadays, the development sills, doors and windows are very fast with advanced technology that expands the materials of sills, doors and windows from traditional wood materials to aluminium. The presence of aluminum material choices make the owner of the house could have a role towards sustainable concept but it is inversely proportional to the real situation in which the use of aluminum frames is widely used by the middle class and above. Yet in terms of time, efficiency and quality is still superior to aluminum frames, aluminum frames in which certain anti-termite, easier maintenance and more durable. This situation is considered as the cost of aluminum door sills and relatively expensive. With so many advantages to the frame, people should start using aluminum frames since it is reasonable to pay a higher price for longer durability.